Biomarkers for Pancreatic Cancer: Is it Ready for Primetime? - Kim, Richard; Mahipal, Amit; Choi, Minsig; Saif, Mohammad Wasif (JOP. Journal of the Pancreas, 2013)
No abstract available. Image: H. Lee Moffitt Cancer Center. Tampa, FL, USA.